Urban spaces and power relations in Roman Egypt - Vasques, Marcia Severina (Romanitas - Revista de Estudos Grecolatinos, 2014)
For a long time, Roman Egypt studies have not been devoted to exploring the Roman influence in the shaping of cities, which is apparently not very evident inside the Egyptian territory. However, this is an issue that has been approached with increasing frequency by historians and archaeologists. Roman Egypt is usually considered as consisting of poleis of Greek foundation, metropolis (capitals of nomos), and villages. We propose to approach the issue of power relations and the formation of urban space in the Egyptian chora, namely Egypt with the exception of the city of Alexandria.